A novel robust edge detection method for full-field modal parameter estimation using an image-based tracking continuously scanning laser Doppler vibrometer system - Lyu, L.F.; Higgins, G.D.; Zhu, W.D. (Mechanical systems and signal processing, 2023)
•A robust edge detection method is developed for a rotating structure.•A two-dimensional scan scheme is developed for its full-field measurement.•A tracking continuous scanning laser Doppler vibrometer system is developed.•An improved demodulation method is used for processing measurement data.•A rotating fan blade with a complex background was tracked and scanned. A novel robust edge detection method is developed for an image-based tracking continuously scanning laser Doppler vibrometer (CSLDV) system to track a rotating structure without attaching any encoder or mark to it and scan its whole surface. The robust edge detection method can extract edges of the rotating structure from its complex background by processing grayscale images of the rotating structure. Once edges of the rotating structure are clearly shown in the processed image, their positions can be easily determined. To track a rotating structure like a rotating blade of a wind turbine with multiple blades, a distance condition is used to determine the position of an edge of the structure that needs to be tracked and estimate its real-time rotation speed. Once the position of the edge of the rotating structure is determined, the image-based tracking CSLDV system can scan the whole surface of the rotating structure via a two-dimensional scan scheme. An improved demodulation method is used to process measured data of response of the rotating structure subject to random excitation and estimate its modal parameters including damped natural frequencies and full-field undamped mode shapes. The robust edge detection method is investigated by tracking and scanning a rotating fan blade subject to random excitation with a complex background using the image-based tracking CSLDV system, and estimating modal parameters of the rotating fan blade with different constant speeds.